An Analysis of 40Gbits/s SDM Transmission over 50 Km Graded-Index Few-Mode-Fiber Using Optisystem - Bhagyalaxmi Behera, Mihir Narayan Mohanty (International Journal of Advanced Science and Technology, 2020)
Few-mode fiber (FMF) based Spatial Division Multiplexing (SDM) is an encouraging technique forsubstantial growth of the spectral-efficiency of current hi-tech optical communication networks.FMFsare the special type of fibers where each guiding mode is treated as a separate data channel. Thistype of multiplexing technique suffers through inter-channel-interference (ICI). The ICI in FMFsarises due to the impairments like mode-coupling and differential-mode-group-delay (DMGD)between the modes. Both of these impairments directly relate to the index differenceneff betweenthe guiding modes. Hence the design of FMFs with low mode coupling, low DMGD, large-effectiveareaAeff  , and low bending-loss for SDM transmission is gaining interest for the researcher.In thiswork, we have proposed a graded-index-few-mode-fiber (GI-FMF) profile that effectively supportsfour linearly-polarized (LP) modes (LP01, LP11, LP21, LP02) with low differential-mode-group-delay(DMGD), low mode coupling, and large-effective-area.